2015
DOI: 10.1177/1555412015624742
|View full text |Cite
|
Sign up to set email alerts
|

Writing “Gamers”

Abstract: In the mid-1990s, a small group of video game designers attempted to lessen gaming's gender gap by creating software targeting girls. By 1999, however, these attempts collapsed, and video games remained a masculinized technology. To help understand why this movement failed, this article addresses the unexplored role of consumer press in defining ''gamers'' as male. A detailed content analysis of Nintendo Power issues published from 1994 to 1999 shows that mainstream companies largely ignored the girls' games m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 30 publications
0
13
0
2
Order By: Relevance
“…Although this fact does not change the nature of the depictions noted, it does perhaps raise questions about the audience. It could be that the ''gamer'' audience continues to be conceived of as solely male (Cote, 2015). Future research should explore expressions of gender in the puzzle and traditional board game genres in that this is a type of play that is more preferred by female game players (Greenberg et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Although this fact does not change the nature of the depictions noted, it does perhaps raise questions about the audience. It could be that the ''gamer'' audience continues to be conceived of as solely male (Cote, 2015). Future research should explore expressions of gender in the puzzle and traditional board game genres in that this is a type of play that is more preferred by female game players (Greenberg et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Se trata de usos ligados a estereotipos que vinculan los hombres a los espacios más técnicos (programación) y las mujeres a los artísticos (escritura). En el caso de las consolas, se observa un estereotipo de género que tiende a vincular a los chicos a lo lúdico y, en especial, a los videojuegos, como ya indicaban investigaciones anteriores (Cote, 2018;Masanet, 2016;Walejko, 2008). Sorprenden las diferencias en relación al uso del 'ordenador de mesa', más utilizado por los chicos.…”
Section: Discussionunclassified
“…Esto acentúa el estereotipo que vincula a las mujeres al uso de los medios para las relaciones interpersonales (Masanet, 2016). Así se confirma también la H5 y que algunas prácticas históricamente masculinas (videojuegos o uso lúdico del ordenador) siguen vigentes (Cote, 2018). En cambio, el consumo y la producción vinculados a lo artístico y expresivo (fotografía, relatos) siguen siendo femeninos.…”
Section: Discussionunclassified
“…Less easy to pinpoint are the more subtle social forces that may steer potential players toward some games and not others, or away from games entirely. To address the gap whereby the barriers to gameplay remain underexplored, I draw on the history of feminist game scholarship that has long illustrated that, although games are frequently marketed in a way that assumes they are of more interest to young boys (Burrill, 2008;Chess, 2017;Cote, 2018), in reality girls often are socialized away from gaming from a young age (de Castell & Bryson, 1998;Harvey, 2015). Interventionist feminist research has shown that when the entry conditions are changed (e.g., the creation of groups where girls can learn to play games in a girls-only environment or in women-led community groups focusing on mentoring other women through designing their own game), girls and women become active players and/or create their own games (Fisher & Harvey, 2013;Fisher, Jenson, & de Castell, 2015;Harvey, 2014;Harvey & Shepherd, 2017;Jenson & de Castell, 2011;Kafai, 2008).…”
Section: Barriers To Digital Gameplaymentioning
confidence: 99%